Empirical investigation of the domain knowledge and team advertising creativity typology: The case of Nescafe coffee. (November 2022) - Bushra, Mazia Fateen; Ahmad, Ayaz; Ahmad, Wisal; Khattak, Zeeshan Zab; Saeed, Imran; Han, Heesup; Ariza-Montes, Antonio
Abstract: This study proposes and tests a typology of domain knowledge and team creativity by empirically assessing the effects of varying levels of domain knowledge on the creative outcomes of the team members. Two separate studies were conducted to address this inquiry. Study one aimed at determining the level of domain knowledge of each team member in the teams. Eleven groups comprising of thirty-three business students designed eleven advertisements for the products of their own choices. Utilizing the situation judgment test and the grade earned in the advertising course, four teams were formed comprising two balanced and two imbalanced domain knowledge teams. To test the hypotheses of the study, these teams were asked to develop a print advertisement for Nescafe for the summer season (Study Two). Upon creativity assessment of the final ads by twenty-six independent creative personnel in a total of seven advertising agencies in Pakistan, the results revealed that a balanced team with low domain knowledge outperformed the other balanced team with high domain knowledge. Further, unexpectedly, one of the imbalanced domain knowledge teams also outperformed the balanced high domain knowledge team. The study in the light of extant literature presents worthwhile implications for academia and practitioners.